Differential expression and subcellular localization of Copines in mouse retina. Issue 14 (28th March 2019) - Goel, Manvi; Li, Tiansen; Badea, Tudor C.
Abstract: Combinatorial expression of Brn3 transcription factors is required for the development of cell‐specific morphologies in retinal ganglion cells (RGCs). The molecular mechanisms by which Brn3s regulate RGC type specific features are largely unexplored. We previously identified several members of the Copine (Cpne) family of molecules as potential targets of Brn3 transcription factors in the retina. We now use in situ hybridization and immunohistochemistry to characterize Copine expression in the postnatal and adult mouse retina. We find that Cpne5, 6, and 9 are expressed in the ganglion cell layer (GCL) and inner nuclear layer (INL) in both amacrine cells and RGCs. Cpne4 expression is restricted to one amacrine cell population of the INL, but is specifically expressed in RGCs in the GCL. Cpne4 expression in RGCs is regulated by Brn3b both cell autonomously (in Brn3b + RGCs) and cell nonautonomously (in Brn3b − RGCs). Copines exhibit a variety of subcellular distributions when overexpressed in tissue culture cells (HEK293), and can induce the formation of elongated processes reminiscent of neurites in these non‐neuronal cells. Our results suggest that Copines might be involved in a combinatorial fashion in Brn3b‐dependent specification of RGC types. Given their expression profile and previously proven role as Ca 2+ sensors, they may participate in the morphogenetic processes that shape RGC dendrite and axon formation at early postnatal ages. Abstract : Copines are a family of Ca 2+ and phospholipid binding proteins that can induce morphological changes reminiscent of neurite formation when overexpressed in tissue culture cells (shown). Within the retina, at least four family members—Copine 4, 5, 6, and 9—are expressed in retinal ganglion, amacrine, and bipolar cells.